Pengaruh Lingkungan Kerja, Motivasi Kerja Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan (Studi Pada Koperasi Unit Desa Pakis Kabupaten Malang) - Nurhasanah Nurhasanah; Budi Wahono; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis research was conduted at the Pakis Village Cooperative Unit, Malang Regency, Jalan Raya Asrikraton Asrikraton Village, Pakis District, Malang Regency. The purpose of this study was to examine and analyze the effect of work environment, work motivation and leadership style on employee performance at the Pakis Village Cooperative Unit, Malang Regency.The variables in this study are work environment, work motivation and ledadership style as independent variables and employeeperformance as the dependent variable in this study. The samples in this study were 36 employees of the Pakis Village Cooperative Unit, Malang Regency. This study uses a quantitative paradigm with an explanatory research approach. Methods of data collection usingprimary data. The analysis used includes instrument testing, classical assumption test, normality test, multiple linier regression with the help of SPSS. The result of this study confirm that the variables of work environment, work motivation and leadership style have a positive and significant effect on the employee performance of the Pakis Village Unit Cooperative, Malang Regency. Keyword: work environment, work motivation leadership style and employee performance.